Preserving and Promoting Saudi Heritage Nationally and Globally: The Role of the Saudi Heritage Commission - Almakaty, Safran Safar (Journal of Ecohumanism, 2025)
This paper is to investigate the pivotal role of the Saudi Heritage Commission in the preservation and promotion of Saudi heritage and culture, both locally and internationally. By addressing the research question, "How does the Saudi Heritage Commission contribute to the preservation and promotion of Saudi heritage?" I explore three sub-questions focusing on local preservation strategies, international cultural promotion efforts, and the measurable impacts of these initiatives. Utilizing a qualitative methodology, It examines various strategies employed by the Commission, including community engagement, technological integration, and cultural diplomacy. The findings reveal a multi-faceted approach that successfully enhances global awareness of Saudi culture while promoting cultural pride and economic benefits. However, challenges such as resource allocation and authentic representation persist, highlighting the need for ongoing evaluation and adaptation. This study contributes to the understanding of cultural heritage preservation and offers insights for similar initiatives worldwide.